Hybridization of several Aerides species and in vitro germination of its hybrid - Chalaparmal, Sivanaswari; Abdullah, Thohirah Lee; Abdul Aziz, Fadelah; Abdullah, Nur Ashikin Psyquay (Academic Journals, 2011)
The wild species of Aerides namely Aerides odorata, A. odorata var.'Yellow', Aerides flabellata and Aerides quinquevulnera var. calayana are fragrant and distributed in Malaysia. Crosses among them attempted to produce primary hybrids which were used to investigate the effects of kinetin and BAP concentrations on seed germination percentage (%) of A. odorata × A. quinquevulnera var. calayana and A. quinquevulnera var. calayana × A. odorata. The total six crosses were: A. odorata var.'Yellow' × A. quinquevulnera var. calayana, A. odorata × A. quinquevulnera var. calayana and A. odorata × A. flabellata and their reciprocals. The highest percentage of successful crosses were between A. odorata var.'Yellow × A. quinquevulnera var. calayana (80%) and lowest were A. flabellata × A. odorata (25%), A. odorata × A. quinquevulnera var. calayana and its reciprocal were 60 and 62%, respectively. Crosses of A. quinquevulnera var. calayana × A.odorata var.'Yellow' and A. odorata and A.flabellata showed 0% success. Pods of A. odorata var.'Yellow' × A. quinquevulnera var. calayana matured at 76 days, A. flabellata × A. odorata at 116 days, A. odorata × A. quinquevulnera var. calayana at 179 days and A. quinquevulnera var. calayana × A. odorata at 184 days. Pods of A. flabellata × A. odorata were the largest and the smallest were A. odorata var.'Yellow' × A. quinquevulnera var. calayana. There was a significant difference in seed germination where the highest germination percentage were with 1.5 mg/L kinetin and the lowest were in 2.0 mg/L BAP for A. odorata × A. quinquevulnera var. calayana. Germination of A. quinquevulnera var. calayana × A. odorata was highest in 1.5 mg/L BAP and lowest in 2.0 mg/L kinetin. Seeds of A. odorata × A. quinquevulnera var. calayana cultured in 1.5 mg/L kinetin took the shortest time for yellowing and greening, 54 and 76 days respectively. 1.0 mg/L kinetin produced first root, as early as 91 days and 1.0 mg/L BAP was the earliest to produce leaf primordial at day 96. The longest time taken for all these stages were in control treatment. The earliest seeds of A. quinquevulnera var. calayana × A. odorata to yellow were at 1.5 mg/L kinetin within 13 days, greening at 1.0 mg/L BAP for 24 days, first root and leaf primordial at 1.5 mg/L BAP at 33 and 54 days respectively. The longest time taken for this species to yellow and green were at control treatment at days 38 and 50, first root in 1.5 mg/L BAP at day 33 and to produce leaf primordia were in 0.5 mg/L kinetin at day 74.